2023
DOI: 10.1093/oncolo/oyad098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Physician-Patient Discordance in Prognostic Perceptions in Advanced Cancer

Abstract: Background Discordance between physicians’ and patients’ prognostic perceptions in advanced cancer care threatens informed medical decision-making and end-of-life preparation, yet this phenomenon is poorly understood. We sought to: (1) describe the extent and direction of prognostic discordance, patients’ prognostic information preferences in cases of prognostic discordance, and physicians’ awareness of prognostic discordance; and (2) examine which patient, physician, and caregiver factors pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
1
1
Order By: Relevance
“…In line, a recent study showed that patients with low fighting spirit were more likely to have prognostic perceptions similar to that of their oncologist. 49 Interestingly, our study showed no influence of patient role preferences on the relation between SDM and adverse outcomes; that is, whether a patient prefers an active v. a rather passive role in decision making does not influence experienced SDM burden as much as we expected. Nonetheless, it is of great importance that oncologists take into account their patients' needs and wants when making a decision, also in regard to their preferred decisional role.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In line, a recent study showed that patients with low fighting spirit were more likely to have prognostic perceptions similar to that of their oncologist. 49 Interestingly, our study showed no influence of patient role preferences on the relation between SDM and adverse outcomes; that is, whether a patient prefers an active v. a rather passive role in decision making does not influence experienced SDM burden as much as we expected. Nonetheless, it is of great importance that oncologists take into account their patients' needs and wants when making a decision, also in regard to their preferred decisional role.…”
Section: Discussioncontrasting
confidence: 41%
“…In line, a recent study showed that patients with low fighting spirit were more likely to have prognostic perceptions similar to that of their oncologist. 49 …”
Section: Discussionmentioning
confidence: 99%